Determinants of Chronic Energy Deficiency (SEZ) of Pregnant Women in DKI Jakarta Urban the Era of Islamic Value-Based Social Development - Sari, Intan Rachmita; Adrian, Verry; Hafili, Ira Nisrawati; Ulfah, Ita Ainy; Andrean, Jessie; Fauziah A, A Rifkah (Pusat Pengkajian dan Pengembangan Islam Jakarta (PPIJ), 2025)
The study aimed to identify the determinants of SEZ among pregnant women in the Jakarta area and formulate intervention strategies that are in line with Islamic principles. This study used data from the DKI Jakarta health information system for the period January - May 2025 with a cross sectional design involving 383 pregnant women. The analysis step formed a logistic regression biner. The results of this study showed that the variables that significantly influenced the variables of Maternal Weight (p=<2e-16), Maternal Height (p=2.88e-07) and Domicile (p=0.0325) significantly influenced the SEZ of pregnant women with the Odds ratio value of Domicile (1.85%), Maternal Weight (26%), Maternal TB (16.1%). Pregnant women who live in areas with high population density OR (1.85) have 84.9% times higher risk of experiencing SEZ than pregnant women who live in areas with low population density. Maternal Weight OR of (0.74) indicates that pregnant women with body weight >145cm have a lower risk of developing SEZ, meaning that the risk of SEZ decreases by 25.6%. Maternal Height OR (1.16) indicates that every increase in the height category of pregnant women was associated with a 16% increase in the risk of developing SEZ. From an Islamic perspective, efforts to maintain maternal and fetal health are an implementation of the Maqasid Sharia principle, namely the protection of the soul (hifz al-nafs) and offspring (hifz al-nasl).